Asset Division Agreement as a Condition for Polygamy Permission: Reformulation of Law Number 1 of 1974 - M. Syam'un Rosyadi; Erfaniah Zuhriah; Ahmad Izzuddin; Hafiza Samath (International Journal of Law, Crime and Justice, 2025)
This study aims to analyze the importance of regulating property division agreements as a requirement in polygamy permit applications, using the approach of Aristotle's theory of justice, as well as maqā ṣ id al- syarī'ah in Islamic law. The type of research is normative, which includes conceptual and philosophical analysis of law, as well as comparative research on property regulation practices in the family law system. The study shows that the practice of polygamy tends to result in economic inequality, neglect of the rights of the first wife and children, and legal conflicts related to the ownership and division of joint property. There are two approaches to property division: equal distribution of property and division of property based on contribution. The results indicate that the contribution-based approach is fairer and more relevant to modern society, especially since women are increasingly involved in household expenses. The principle of sadd al-dzarī'ah also states that this agreement is very important as a preventive measure against possible damage that occurs in the household. Practically, this study proposes the implementation of regulations in state law to require property division agreements as a formal requirement in polygamy permit applications. Combining western and Islamic values of justice within a socially just family law framework is the main focus of this research.